1990
DOI: 10.2151/jmsj1965.68.1_37
|View full text |Cite
|
Sign up to set email alerts
|

Convective and Stratiform Components of a Winter Monsoon Cloud Cluster Determined from Geosynchronous Infrared Satellite Data

Abstract: A technique originally devised by Adler and Negri (1988) for estimating the convective and stratiform precipitation areas and amounts of mesoscale convective cloud systems from infrared satellite imagery has been applied to a large cloud cluster observed over the South China Sea during the Winter Monsoon Experiment (WMONEX). The technique was modified to obtain agreement with a previous analysis of ground-based radar data obtained in a limited part of the cluster. The modifications included altering the method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…For tropical cloud systems, this algorithm estimates surface rainfall rates and the area of convective and stratiform regions. Goldenberg et al (1990) modified the empirical ''discrimination line'' of Adler and Negri (1988) and applied it to WMONEX data. Kikuchi (1994) also applied this method to GMS imagery in TOGA-COARE.…”
Section: Estimation Of Cloud Area and Rainfallmentioning
confidence: 99%
“…For tropical cloud systems, this algorithm estimates surface rainfall rates and the area of convective and stratiform regions. Goldenberg et al (1990) modified the empirical ''discrimination line'' of Adler and Negri (1988) and applied it to WMONEX data. Kikuchi (1994) also applied this method to GMS imagery in TOGA-COARE.…”
Section: Estimation Of Cloud Area and Rainfallmentioning
confidence: 99%
“…If there is more than one Tmin in a pixel, the closest to the center of the pixel is chosen as Tmin. After that is a calculation of the slope parameter value (S) based the value of BT at a point estimated by 8 points surrounding the equation (Islam et al, 2002) According to Goldenberg et al (1990), in the identification of convective core, the S value must meet the following threshold.…”
Section: B Cstmentioning
confidence: 99%
“…The original form of CST used in this study applies rainfall estimation steps similar to the procedures proposed by Adler and Negri [1], Goldenberg, et al [2] and Islam, et al [4]. The estimation actions include, among others, the application of techniques to identify convective cores and their locations, utilizing IR imagery from geostationary meteorological satellites (GMS), and determination of the intensity of convective and stratiform rain.…”
Section: The Original Form Of Cstmentioning
confidence: 99%
“…According to Goldenberg, et al, [2], to distinguish convective cores at the identified location, the criteria as shown by Eq. (3) should be fulfilled:…”
Section: The Original Form Of Cstmentioning
confidence: 99%
See 1 more Smart Citation